Identification of a candidate proteomic signature to discriminate multipotent and non-multipotent stromal cells. - Michael Rosu-Myles; Yi-Min She; Joel Fair; Gauri Muradia; Jelica Mehic; Pablo Menendez; Shiv S Prasad; Terry D Cyr (PLoS ONE, 2012)
Bone marrow stromal cell cultures contain multipotent cells that may have therapeutic utility for tissue restoration; however, the identity of the cell that maintains this function remains poorly characterized. We have utilized a unique model of murine bone marrow stroma in combination with liquid chromatography mass spectrometry to compare the nuclear, cytoplasmic and membrane associated proteomes of multipotent (MSC) (CD105+) and non-multipotent (CD105-) stromal cells. Among the 25 most reliably identified proteins, 10 were verified by both real-time PCR and Western Blot to be highly enriched, in CD105+ cells and were members of distinct biological pathways and functional networks. Five of these proteins were also identified as potentially expressed in human MSC derived from both standard and serum free human stromal cultures. The quantitative amount of each protein identified in human stromal cells was only minimally affected by media conditions but varied highly between bone marrow donors. This study provides further evidence of heterogeneity among cultured bone marrow stromal cells and identifies potential candidate proteins that may prove useful for identifying and quantifying both murine and human MSC in vitro.